Significance of Endogenous Antimicrobial Peptides on the Health of Food Animals - Fasina, Yewande O.; Obanla, Temitayo; Dosu, George; Muzquiz, Sierra (Frontiers in Veterinary Science, 2021)
Acquired resistance to in-feed antibiotic growth promoters continues to be an imperative problem in the livestock industries, thereby necessitating continuous pursuit for alternatives. Antimicrobial peptides (AMPs) are one of the critical host innate immune responses to invading microbial pathogens. AMPs such as cathelicidin and β-defensins have a broad-spectrum activity against Gram-negative and Gram-positive bacteria and even the multi drug resistant bacteria, and can also provide additional immunomodulatory activities to the host. In this review, we provide an overview of the potential of endogenous (natural) antimicrobial peptides (originating primarily from the gastrointestinal tract) to serve as alternatives to the use of prophylactic antibiotics for disease control in food animals.